2005
DOI: 10.1142/s0217751x05020926
|View full text |Cite
|
Sign up to set email alerts
|

Energy–momentum in Viscous Kasner-Type Universe in Bergmann–thomson Formulations

Abstract: Abstract. Using the Bergmann-Thomson energy momentum complex and its teleparallel gravity version, we obtain the energy and momentum of the universe in viscous Kasner-type cosmological models. The energy and momentum components (due to matter plus field) are found to be zero and this agree with a previous work of Rosen and Johri et al. who investigated the problem of the energy in Friedmann-RobertsonWalker universe. The result that the total energy and momentum components of the universe in these models is zer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
10
47
0
Order By: Relevance
“…Virbhadra [13], using the energy and momentum complexes of Einstein, Landau-Lifshitz, Papapetrou and Weinberg for a general non-static spherically symmetric metric of the Kerr-Schild class, showed that all of these energy-momentum formulations give the same energy distribution as in the Penrose energy-momentum formulation. Recently, The problem of energy-momentum localization was also considered in alternative gravitation theory, namely teleparallel gravity [10,21]. The authors found that energy-momentum also localize in this alternative theory, and their results agree with some previous papers which were studied in the general theory of relativity.…”
Section: Introductionsupporting
confidence: 63%
“…Virbhadra [13], using the energy and momentum complexes of Einstein, Landau-Lifshitz, Papapetrou and Weinberg for a general non-static spherically symmetric metric of the Kerr-Schild class, showed that all of these energy-momentum formulations give the same energy distribution as in the Penrose energy-momentum formulation. Recently, The problem of energy-momentum localization was also considered in alternative gravitation theory, namely teleparallel gravity [10,21]. The authors found that energy-momentum also localize in this alternative theory, and their results agree with some previous papers which were studied in the general theory of relativity.…”
Section: Introductionsupporting
confidence: 63%
“…The authors [30][31][32][33][34][35][36] showed that energymomentum can also be localized in this theory. It has been shown that the results of the two theories can agree with each other.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some authors [30][31][32][33][34][35][36] argued that this problem of energy may be settled in the context of teleparallel theory (TPT) of gravity. They showed that energy-momentum can also be localized in the framework of this theory.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have extended these results to other complexes [11], anisotropic cosmologies [12][13][14][15][16][17], and teleparallel gravity (a modification of general relativity) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%